Assessment of consumption of medicines of drugs in conditions of stationary treatment children with acute respiratory viral infections - I. A. Narkevich; V. N. Timchenko; O. D. Nemyatykh; D. D. Siukaeva; T. M. Terninko; G. S. Melnikova (LLC "Diagnostics and Vaccines", 2020)
The purpose of the study was to analyze the structure of drug consumption in the conditions of inpatient treatment of children with acute respiratory viral infections to optimize treatment standards and reduce material costs. The paper presents the results of a retrospective study of the consumption of drugs in the inpatient treatment of children with acute respiratory viral infections. It is shown that the most vulnerable group for the occurrence and development of acute respiratory viral infections is represented by children aged 1 year to 7 years (60.0% of the total population). Evaluation of drug consumption suggests that the frequency of prescriptions is dominated by J01 category «Antibacterial drugs for systemic use» and R01 «Nasal preparations» (18.58% and 16.56%, respectively). At the same time, the group L03 «Immunostimulants» makes a significant contribution to the consumption structure according to the frequency of appointments, covering 9.31%.